The Effect of Multidimensional Spiritual Intervention on Cortisol, and Disease Perception After Vascular Bypass Surgery - Fatemeh Nequee; Masud Janbozorgi (مطالعات اسلام و روانشناسی, 2022)
The aim of this study was to investigate the effect of multidimensional spiritual intervention on salivary cortisol. Perception of the disease and psychological disturbances of patients with coronary artery bypass graft surgery. The study was a quasi-experimental study with a control group and a pre-test-post-test design with one-month and three-month follow-up. The statistical population of this study includes patients who had coronary artery bypass graft surgery and referred to the Rehabilitation Center of Tehran Heart Hospital. Thirty subjects were selected by convenience sampling method and randomly assigned to experimental and control groups. The instruments of this study were the 21DASS-questionnaire, salivary cortisol kit and IPQ-R disease perception. The experimental group was exposed to the independent variable (multidimensional spiritual intervention) in 10 sessions of 90 minutes. Multivariate analysis of covariance and SPSS software were used to analyze the data. The results show that between the mean scales of pre-test, post-test and follow-up, disease perception (F = 211,168, p <0.001), salivary cortisol (F = 89.43, <0.001) p), stress (F = 251.191, p <0.001), anxiety (F = 209.896, p <0.001) and depression (F = 143.04, p <0.001) significant difference between There is an experimental group and a control group. Therefore, according to the results of the study, it can be claimed that multidimensional spiritual intervention of salivary bercortisol, disease perception and psychological disorders of patients have been effective.